2017
DOI: 10.1038/srep46350
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced resistive switching characteristics in Pt/BaTiO3/ITO structures through insertion of HfO2:Al2O3 (HAO) dielectric thin layer

Abstract: An enhanced resistive switching (RS) effect is observed in Pt/BaTiO3(BTO)/ITO ferroelectric structures when a thin HfO2:Al2O3 (HAO) dielectric layer is inserted between Pt and BTO. The P-E hysteresis loops reveal the ferroelectric nature of both Pt/BTO/ITO and Pt/HAO/BTO/ITO structures. The relation between the RS and the polarization reversal is investigated at various temperatures in the Pt/HAO/BTO/ITO structure. It is found that the polarization reversal induces a barrier variation in the Pt/HAO/BTO interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…To perform the photovoltaic characterization, indium tin oxide (ITO) top electrodes with a diameter of 1 mm were deposited by ion-beam sputtering deposition (IBSD), as described in ref. 41 , while Aluminium electrodes were attached to the Si wafer backside by electric spark. Current-voltage (I-V) characteristics, both in the dark and under light illumination, with a maximum power density of 100 mWcm −2 (AM 1.5 G) were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…To perform the photovoltaic characterization, indium tin oxide (ITO) top electrodes with a diameter of 1 mm were deposited by ion-beam sputtering deposition (IBSD), as described in ref. 41 , while Aluminium electrodes were attached to the Si wafer backside by electric spark. Current-voltage (I-V) characteristics, both in the dark and under light illumination, with a maximum power density of 100 mWcm −2 (AM 1.5 G) were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…3 Furthermore, most research studies have concentrated on the Nd 3+ ions due to their efficient infrared emissions by the three transitions 4 F 3/2 / 4 I 9/2 , 4 F 3/2 / 4 I 11/2 and 4 F 3/2 / 4 I 13/2 with emissions at wavelengths around 946, 1064 and 1350 nm which nds potential applications in the elds of laser and infrared optical communications. 4 Indeed, many studies have demonstrated an appreciable enhancement of the spectral analysis of Nd 3+ ions. G. Singh et al 5 reports that the emissions of neodymium in lead lanthanum zirconate titanate (Pb 0.91 La 0.08 (Zr 0.65 Ti 0.35 ) 0.98 O 3 ) have been extensively studied owing to their excellent luminescence properties and proper energy separation towards a potential application in the elds of laser and infrared optical communications.…”
Section: Introductionmentioning
confidence: 99%
“…The diffraction peaks at 31.5 0 and 31.6 0 corresponded to (110) and (110) planes, 33 respectively. The weak diffraction patterns of CrBTO are shown in the inset of Fig 1(a) which may be due to a nanoscale thickness of films which was hard to detect by powder XRD machine.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…Here, the work function of the top Au electrode and bottom ITO electrode is 5.1 eV and 4.5 eV. 37 The electron affinity and energy band gap of the CrBTO is used as 3.8 eV and 3.4 eV, respectively 38 which are obtained from earlier reports. On the pristine device, the potential barrier height is ∼1.3 eV.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%